“Teaching-Learning” Inter-Action Between autoreferentiality, neurophenomenology, self-aware experience and knowledge - Pastena, Nicolina (Formazione & insegnamento, 2014)
With the advent of the so-called science of complexity a new thinking reasoning originated, which places the dimensions of logic and time at the centre of philosophical and speculative interests, and particularly, has led to a different interpretation of the concept of time. Ilya Prigogine, in his interesting work From Being to Becoming (1986) deals with this theme, identifying a form of temporality which he defines “creative time.” Prigogine, in explaining his theory, wanted to demonstrate that life does not simply consist of the execution of a pre-determined programme but is rather defined within a recursive cycle – meant as creation of something new, as an invention. We have before us a creator time which requires its own particular logic: the logic of non-linearity, better defined as logic of complexity. In this view, contemporary scientific rationality is shown as a reasoning in which universalizing principles do not exist, neither a globality of basic concepts exists, nor a universality of methods applicable to all fields of knowledge. The pillar of this conception is found in the shift from intellectual ability to cognitive strategies. In brief, while intellectual abilities are learned in situations of objectivation of the teaching-learning processes and are translated into objectively verifiable applications, the possibility of learning cognitive strategies is linked to a non-linear logic. These are taught through non-linear didactics (designed to favour autoreferentiality) in a field of subjectivation of educative processes.